2018
DOI: 10.1126/sciadv.aau1935
|View full text |Cite
|
Sign up to set email alerts
|

The CCT chaperonin is a novel regulator of Ca 2+ signaling through modulation of Orai1 trafficking

Abstract: A chaperone complex (CCT) regulates the trafficking of a calcium channel (Orai1) and, as such, modulates cellular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 56 publications
5
31
0
Order By: Relevance
“…Of all the identified proteins, we were specifically intrigued by the enrichment of CCT2 in UC-MSC-EVs because of its reported modulation of Ca 2+ channels trafficking ( Figure 5B,C). [34,35] Our Western blotting analysis also confirmed that both UC-MSC-EVs and UC-MSCs contained high Figure 2. UC-MSC-EVs improve liver IRI and regulate CD154 expression on CD4+ T cells in vitro and in vivo.…”
Section: Cct2 Derived From Uc-msc-evs Reduces Cd154 Synthesis Of Cd4+supporting
confidence: 67%
“…Of all the identified proteins, we were specifically intrigued by the enrichment of CCT2 in UC-MSC-EVs because of its reported modulation of Ca 2+ channels trafficking ( Figure 5B,C). [34,35] Our Western blotting analysis also confirmed that both UC-MSC-EVs and UC-MSCs contained high Figure 2. UC-MSC-EVs improve liver IRI and regulate CD154 expression on CD4+ T cells in vitro and in vivo.…”
Section: Cct2 Derived From Uc-msc-evs Reduces Cd154 Synthesis Of Cd4+supporting
confidence: 67%
“…Further evidence supporting the important role of CCT in cell cycling come from studies showing that key cell cycle mediators like Cdc20 44 , CDK2/cyclin E 45 , Polo-like kinase 1 (PLK1) 46 and others are folded and assembled by CCT 30,33 , which in part explains why CCT levels increase during S phase 47 . Moreover, the CCT chaperonin was recently found to have role in the disassembly of mitotic checkpoint complexes 48 as well as mediating calcium signaling through Orai1 trafficking 49 . Our finding that overexpressing CCT2 promoted the proliferation of breast cancer and breast epithelial cells is among the first to demonstrate that an increase in cancer cell growth and upregulation of select CDKs as well as other CCT subunits resulted from overexpressing this single CCT subunit.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has identified a major role for the intracellular loop in Orai1 involving amino acids 157–167 in regulation of channel trafficking ( 13 ). This region was found to interact with the chaperonin-containing TCP-1 complex (T-complex protein) chaperonin complex to modulate Orai1 endocytosis.…”
Section: Discussionmentioning
confidence: 99%